PENERAPAN MODEL LOG LINIER TERHADAP PERSEPSI MAHASISWA PADA SINETRON RELIGIUS : APPLICATION OF THE LINEAR LOG METHOD TO STUDENT PERCEPTION ON RELIGIOUS SINETRON - Azwar Habibi (Jurusan Matematika, Fakultas Teknik, Universitas Bangka Belitung, 2023)
The purpose of this study is to find out which variables in the cell cause the contingency to be dependent in the case of student perceptions in religious soap operas. The data taken from this study are the results of a survey of IAIN Madura students with the variables having experienced events, gender and deepening religious knowledge. The data analysis method used is Linear Log Model. The conclusions in this study are as follows based on the estimated parameter values ​​presented in the table above, it can be seen that male and female IAIN MADURA students believe that religious soap operas can deepen religious knowledge, and also male and female students believe that religious soap operas cannot deepen religious knowledge. Based on the Chi Square values ​​presented in the table above, it can be seen that the opinion variable, deepening religious knowledge and having experienced an incident have no relationship or each variable is independent, so it cannot be continued to a linear logistic test.